CSVDataMerge: A Simple and Free Program for Concatenating Experimental Data Files. (10th December 2021) - Schmidt, James R.
In experimental psychology and other applications, researchers will often have numerous datafiles (e.g., one for each participant) that need to be joined together into one larger dataset before data analyses. Many experimental software programs, including some increasingly popular ones (e.g., PsychoPy or OpenSesame), do not include data merging functionality. Copy-and-pasting (potentially error prone) or the writing of situation-specific scripts (potentially difficult and time consuming) may be necessary. CSVDataMerge was created as a free Java application that merges CSV (or comma-separated TXT) data with little more than a double-click. The program also appropriately deals with datasets that have different column orders in different datafiles or empty cells. More trivially, it can also concatenate datafiles that do not contain headers and allows the user to specify which columns to keep and in what order.